Emotional Impact of COVID-19 Lockdown Among the Spanish Population - Gismero-González, Elena; Bermejo-Toro, Laura; Cagigal, Virginia; Roldán, Angustias; Martínez-Beltrán, María Jesús; Halty, Lucía (Frontiers in Psychology, 2020)
The COVID-19 pandemic has resulted in some populations being confined to their homes as part of infection control measures. This situation can be hard to cope with due to separation from loved ones, prohibition of regular activities, fear of infection, loss of freedom, and so on. These negative impacts cause considerable psychological stress, and all the more so when the situation continues for an extended period, as was the case in Spain. The aim of this study was to learn about the emotional impact of 8 weeks of quarantine measures on the Spanish population and the consequent effects, if any, of certain demographic variables (age, sex), health habits (physical exercise, following a routine, smoking), and protective factors (perceived social support, resilience). Methods 906 Spanish adults completed an online questionnaire to gather information about their prevailing mood and affects (before and after 8 weeks of lockdown), using the Positive and Negative Affect Schedule (PANAS) (Watson et al., 1988), and other variables related to their habits and protective factors. Findings As expected, the data indicated an increase in negative affects (e.g., “upset”, “afraid”, “distressed”) and a decrease in positive affects after 8 weeks under lockdown, as well as a general decline in overall mood. The largest increases in negative affects were observed in young adults (18–35 years) and women. We did not find any differences between people who were or were not diagnosed with COVID-19. Adhering to a routine, maintaining the same weight, and moderate physical exercise were associated with fewer negative affects, which indicates they are important protective factors, as are perceived social support and resilience. Conclusions In order to mitigate the psychological impact of confinement, it is important to develop psychoeducational measures that encourage subjects to adhere to health habits and promote social support and resilience as protective factors. A special preventive focus should be placed on the most vulnerable population groups, namely women and young adults. For a public health lockdown to succeed, its negative consequences must be minimized insofar as possible through adequate knowledge of the risk factors and protective factors, and by means of prevention-oriented organization.